Carta de Rafael Arrillaga Roqué - Todd, Roberto H.; Arrillaga Roqué, Rafael (My University, 1924)
La reunión del Comité Territorial Republicano.
Keywords: Partido Republicano (Puerto Rico); Tous Soto, José, 1874-1933